Controllable Microfluidic Fabrication of Microstructured Materials from Nonspherical Particles to Helices. Issue 23 (1st September 2017) - Wang, Wei; He, Xiao‐Heng; Zhang, Mao‐Jie; Tang, Meng‐Jiao; Xie, Rui; Ju, Xiao‐Jie; Liu, Zhuang; Chu, Liang‐Yin
Abstract: This work reports on a facile and flexible strategy based on the deformation of encapsulated droplets in fiber‐like polymeric matrices for template synthesis of controllable microstructured materials from nonspherical microparticles to complex 3D helices. Monodisperse droplets generated from microfluidics are encapsulated into crosslinked polymeric networks via an interfacial crosslinking reaction in microchannel to in situ produce the droplet‐containing, fiber‐like matrices. By stretching and twining the dried fiber‐like matrices, the encapsulated droplets can be flexibly engineered into versatile shapes for template synthesis of controllable nonspherical microparticles and helices. Moreover, magnetic helices can be fabricated by simply dispersing magnetic Fe3 O4 nanoparticles in the droplets to achieve rotational and translational motion under a rotated magnetic field. This work provides a simple and versatile strategy for the template synthesis of advanced functional microstructured materials with flexible shapes. Abstract : Controllable microstructured materials from flexible nonspherical microparticles to helices are fabricated from controllably deformed droplets encapsulated in fiber‐like polymeric matrices. By stretching and twining the fiber‐like matrix, the encapsulated droplets can be flexibly deformed for template synthesis of versatile nonspherical microparticles and complex 3D helices. This work provides a flexible strategy for developing advanced functional microstructured materials.